Trace Operators on Wiener Amalgam Spaces. (8th May 2016) - Cunanan, Jayson; Tsutsui, Yohei
Abstract : The paper deals with trace operators of Wiener amalgam spaces using frequency uniform decomposition operators and maximal inequalities, obtaining sharp results. Additionally, we provide the embedding between standard and anisotropic Wiener amalgam spaces.